RISE OF CHINA AND ITS INFLUENCE ON THE WORLD AND REGIONAL ORDERS. COMPARATIVE ANALYSIS: PROCEEDINGS OF THE ROUNDTABLE DISCUSSION - A. D. Voskressenski (Сравнительная политика)
Proceedings of the roundtable “Regional Orders and the Rise of CHINA”, organized in the framework of the RISA Convention on October 21, 2019 at MGIMO University.